Makna Tartil dalam Al-Qur’an Surah Al-Muzzammil Ayat: 4 (Studi Komparatif: Tafsir Al-Munir, Tafsir Al-Qurtubi, Tafsir At-Thabari) - Hsb, Miswar Hamdani (TSAQOFAH, 2024)
This Journal Is Entitled The Meaning Of Tartil In The Qur'an Surah Al-Muzzammil Ayat: 4 (Comparative Study: Tafsir Al-Munir, Tafsir Al-Qurtubi, Tafsir At-Thabari), which discusses what the meaning of tartil is according to the Ulama', the community and especially according to the Ulama' interpretations that the author chose, namely Wahbah Az-Zuhaili, At-Thabari and Imam Al-Qurtubi, and this research was researched using library research by collecting data related to this research, then explained based on the data provided obtained. The data collection technique used is by collecting related books, scriptures and articles. And using a comparative interpretation method, namely by listing three interpretations from different books and then analyzing them and examining the differences and similarities in the problem. In this research, the formulation of the problem is: what is the meaning of tartil in the Al-Qur'an which is generally understood by the public, what is the meaning of tartil in the Al-Qur'an according to Ulama' in general, what is the meaning of tartil in the Al-Qur'an surah Al -Muzzammil verse 4 according to the teachings of Az-Zuhaili, Imam Al-Qurtubi, and Imam At-Thabari in their respective Tafsir. The results of this research show that the meaning of tartil which is generally understood by the public as reading the Al-Qur'an which is read slowly, among the public in general is only limited to the meaning slowly without exploring the meaning of tartil in detail, and as for tartil according to the Ulama', one of whom is Imam Al-Razi, namely, tartil is a confirmation of the obligatory command of tartil for qari (readers), namely the obligation to read slowly and recite clearly and give meaning to the reading, and Imam Al-Razi also quotes the opinion of Imam Az -Zajjaj regarding the meaning of tartil, namely "Reading clearly in each letter, whereas according to the imams the interpretation chosen by the author himself, namely the first, according to Wahbah Az-Zuhali tartil in Al-Munir's book of commentary is "Read the Qur'an slowly by explaining the letters, this will help to understand the Qur'an and reflect on it." (Wahbah Az-Zuhaili interprets slowly by explaining the letters to understand and contemplating the Al-Qur'an, the second according to Imam Al-Qurtubi is "Do not rush in reading the Al-Qur'an, but read it carefully, slowly, and also reflect on the meaning of what you read", the third According to Imam At-Tabari, "explain the contents of the Qur'an when you read it, and read it tartly and well."